Effects of Stress and Burnout on Rural Bank Workers in Ghana by Gender and Rank: Exploring Coping Strategies. - Eyiah-Bediako, Sylvia; Gyasi, Isaac (Human Resource and Leadership Journal, 2025)
Purpose. The study examined the effects of stress and burnout on rural bank workers in Ghana by gender and rank: exploring coping strategies. Methodology. Descriptive survey was used for the study. The instrument used for the study was a questionnaire and it was made up of two sections. Section A included three items that assessed demographic characteristics of the respondents. Section B included 10 items that evaluate various strategies for coping with stress and burnout. The accessible population for the study was 148 rural bank workers selected from four (4) rural banks with a sample size of 108. Sixty-eight (68) males and forty (40) female workers were selected for the study. Proportional sampling was used to determine the total number of respondents from each rural bank. Data were analysed using descriptive statistics (means and standard deviation) and inferential statistics (multiple linear regression and multivariate analysis of variance (MANOVA). Findings. The study revealed that flexible shifts, adequate staffing, good leadership and availability of resources are appropriate strategies that help them to cope with the stress and burnout related to their work. It is also revealed that workers experience the same level of stress and burnout irrespective of their gender. Unique contribution to theory, practice and policy: the study conclude that the level of stress and burnout do not differ based on the ranks. It was recommended that when providing treatment or management services for rural bank workers emphasis should not be placed on the gender and rank since the levels of stress and burnout experience are the same. It can be concluded that high stress and burnout among bank workers leads to poor output on their job. Again, strategies such as flexible shifts, adequate staffing, and better working conditions